Diplomasi Publik Indonesia terhadap Sustainable Tourism Kompleks Candi Borobudur dan Prambanan - Adinda Dilah Suri; Hasan Sidik (Jurnal Hubungan Internasional, 2021)
This paper aimed to provide an overview of Indonesia’s public diplomacythrough the World Heritage Twin Programme on developing sustainabletourism and preserving the Borobudur and Prambanan Temple Compounds.Every World Heritage Sites in the world should apply the concept of sustainabletourism. We should maintain it, so its identity and value do not disappear. Fromthe given background, this paper focuses on how Indonesia’s public diplomacycould help develop sustainable tourism and preserve the Borobudur andPrambanan Temple Compounds. The author uses the qualitative researchmethod to examine the issue with primary and secondary data sources frominterviews with the expert and study of literature. The author’s analysisshows some aspects, both from sustainable tourism and preservation, that themanager does not fulfill yet. However, as one of the forms of Indonesia’s publicdiplomacy, World Heritage Twin Programme can help achieve those aspectsand help develop sustainable tourism and preservation of Borobudur andPrambanan Temple Compounds.